Perception of professional competence of business studies teachers and students’ academic performance in Nigeria: The industrial relations approach - Akintola, Olugbenga Adeyanju; Fejoh, Johnson; Adeyemi, Adedayo Patrick; Oluwo, Oluwabunmi Amos (Journal of Education in Black Sea Region, 2022)
The goal of this research was to investigate the professional competence of business educators as the determinant of academic performance of junior secondary school students in Ijebu-North Local Government area of Ogun state, Nigeria. This study investigated the professional competence of business educators as determinants of academic performance of selected junior secondary school students in Ijebu-North Local Government Area of Ogun state, Nigeria. Two hypotheses were formulated and tested. The study was correlational in nature using survey research design. Stratified random sampling technique was used to select twenty respondents from twenty schools, totaling 400 sample of the study. A structured questionnaire was used for data collection and it consisted of two (2) sections. Data were analysed using descriptive and inferential statistics. Pearson Correlation and independent t–test were used in analyzing the hypotheses. Findings revealed that there was a significant relationship between teachers’ professional competence and students’ performance in business studies. Furthermore, there was no significant gender difference in the students’ perception of their teachers’ professional competence. Based on the findings, it was recommended among others that professional body (Association of Business Educators of Nigeria) should be bold enough to collaborate with employers of business educators to carryout performance audit in order to reduce the prevalence of below-standard teachers in this profession and strengthening the roles of universities in the preparation of professional business studies teachers.